Sosialisasi Pemanfaatan Sosial Media Sosial Sebagai Sarana Promosi Produk Umkm di Desa Pentadio Timur Kecamatan Telaga Biru Kabupaten Gorontalo - Muchlis, Moh Muchlis Djibran; Dewa Oka Suparwata; Aditya Djaini; Elvin Sukri Tangio; Femi Umar; Sukirman Ishak; Voni Arman Ajuba; Anisa Kasim; Putri Ramdhini Potale; Humaira A Musa; Sriyulianti Humolungo; Panji Sukma (Universitas Pahlawan Tuanku Tambusai, 2024)
This socialization was carried out with the aim of providing an understanding of the use of Social Media as a means of product promotion for the community and MSME actors in East Pentadio Village. In this activity, participants were given hands-on training and demonstrations on how to utilize social media for MSME promotion. The results of the activity The results showed that participants had the knowledge and skills to create video content and share it on social media as a means of promoting MSME. Content will be shared in social media as a means of promoting MSME products. This activity is very important in increasing community awareness and ability to use social media to promote MSME products. in using social media to promote MSME products.